Labor Picketing Centre Plaza Holiday Inn - Watkins, Howard::::::::: (1983)
Luisa Medina, Chris Petersen, Esther Padilla holding 'On Strike Unfair Labor Practice" signs for Culinary Union Local 62 Centre Plaza hotel entrance in background; Ventura Street side